التحرير والتحبير شرح رسالة ابن أبي زيد القيرواني: دراسة وتحقيق لأبواب من الطهارة - رملي، عبدالله علي سالم (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research revolves around Imam Taj al-Din al-Fakihani (D 734H) and the manuscript of his work al-Taḥrir wa al-Taḥbir which is an explanation of the book Risalah of Ibn Abi Zayd al-Qayrawani. The researcher chose to examine this exactly manuscript as a subject for his research for two reasons: first, the academic value which this explanation possess, and second, the academic role the Imam holds among his peers as he was one of the major scholars of his time and which Maliki Scholars had narrated massively from him. The researcher has divided his research into two parts in addition to the proposal of the research: 1. The analytical section and 2- The examination section. In the first section, the researcher introduces Ibn Abi Zayd al-Qayrawani, his scholars, and his works, followed by the introduction of his work Al-Resalah and its academic role. In addition, the researcher introduces Imam Taj al-Din al-Fakihani, his scholars, and his works along with the approach that the Imam used in producing his explanation on Al-Resalah and then introduces his work al-Taḥrir wa al-Taḥbir with its academic role. The second section tackles the examined text by examining two chapters of the section Al-Tahara (Purification) by following the principles of examination set by the experts and worked to verify the text accurately and to producing it with no errors and distortion as much as possible. Of the most important findings by the researcher are, first, the display of the position of Imam Taj al-Din al-Fakihani among the scholars of his era, and his opinions were widely quouted and refered to inside the Madhhab as his work was a major work used by those who explained Risalah after him, and second, the distinct style of this valuable work as it expanded in mentioning the dispute inside Madhhab al-Maliki and outside of it with the mention of evidences and the principles of jurisprudence and basics.